2016
DOI: 10.1002/ajh.24268
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the noninvolved pair of the myeloma isotype correlates with poor survival in newly diagnosed and relapsed/refractory patients with myeloma

Abstract: Heavy light chain (HLC) assays allow precise measurement of the monoclonal and of the noninvolved polyclonal immunoglobulins of the same isotype as the M‐protein (e.g., monoclonal IgAκ and polyclonal IgAλ in case of an IgAκ myeloma), which was not possible before. The noninvolved polyclonal immunoglobulin is termed ‘HLC‐matched pair’. We investigated the impact of the suppression of the HLC‐matched pair on outcome in 203 patients with multiple myeloma, a phenomenon that likely reflects the host's attempt to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 30 publications
1
61
0
3
Order By: Relevance
“…The serological and bone marrow tests measured secreted protein and abnormal plasma cells, respectively. HLCr/FLCr analysis could indicate the functional output from residual healthy plasma cells, with recovery or preservation of polyclonal immunoglobulins improving outcomes in myeloma patients (Kastritis et al , ; Ludwig et al , ). Improved sensitivity of serological tests could result in a better correlation with MFC MRD testing.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…The serological and bone marrow tests measured secreted protein and abnormal plasma cells, respectively. HLCr/FLCr analysis could indicate the functional output from residual healthy plasma cells, with recovery or preservation of polyclonal immunoglobulins improving outcomes in myeloma patients (Kastritis et al , ; Ludwig et al , ). Improved sensitivity of serological tests could result in a better correlation with MFC MRD testing.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…IgGκ/IgGλ). [6][7][8] As yet, the possible impact of CAs on Ig and FLC subtypes and their levels is poorly studied in MM.…”
mentioning
confidence: 99%
“…Another similar study conducted by Pruzanski et al [9] showed that the degree of suppression of uninvolved immunoglobulins was related to worsened prognostic factors, but its effect on survival was not assessed. In contrast to the abovementioned papers, 2 studies [6,7] reported that the suppression of other isotypes (e g, IgA, or IgM for IgG-kappa myeloma) could not affect patients' outcome. Nonetheless, the level of uninvolved pair of monoclonal immunoglobulins (e g, IgG-lambda for IgG-kappa myeloma) was related to poorer survival.…”
Section: Discussionmentioning
confidence: 89%
“…The effect of suppression of uninvolved isotypes on the outcome of cases was previously studied and there was controversy in the results of the former works. In some studies, it was related to poorer outcome [3][4][5] and in others it did not affect patients' outcomes [6,7]. However, in previous studies the effect of treatment type on the outcome of cases was not evaluated concurrently.…”
Section: Introductionmentioning
confidence: 99%